Reading behaviour and the influence of reading on the English Language proficiency at UiTM Sabah / Jocelyn Lee Yee Vun, Dorothy Chin and Xavier Thayalan - Lee, Jocelyn Yee Vun; Dorothy, Chin; Thayalan, Xavier (Institute of Research, Development and Commercialization (IRDC), 2007)
In general, UiTM students are often said to be weak in the English Language. In this study, the students home and their former school experience, their motivations and attitudes towards their English Language proficiency were investigated Pre-diploma students answered the questionnaires and the data were analysed by looking into the frequency count, mean, standard deviation and correlations between the variables. The results ofthe analysis displayed that homes and schools ofthe respondents were the contributing factors to their English Language competency. The implications of these results are discussed